Relations between occupational exposure to coal mine dusts, erythrocyte catalase and Cu++/Zn++ superoxide dismutase activities, and the severity of coal workers' pneumoconiosis. Issue 8 (August 1998) - Nadif, R; Bourgkard, E; Dusch, M; Bernadac, P; Bertrand, J P; Mur, J M; Pham, Q T
Abstract : OBJECTIVES: To better understand the relations between occupational exposure, blood antioxidant enzyme activities, total plasma antioxidant concentration, and the severity of coal workers' pneumoconiosis (CWP). METHODS: Blood samples were obtained from miners without CWP exposed to low dust concentrations for > or = 4 years at the time of the study (n = 105), or exposed to high dust concentrations for > or = 14 years at the time of the study (n = 58), and from retired miners with CWP (n = 19). Miners without CWP were classified into three subgroups according to their estimated cumulative exposure to dust. Chest x ray films were obtained for each miner. Miners were classified in five subgroups according to their International Labour Organisation (ILO) profusion grades. Univariate tests were completed by multiple linear regression analyses. RESULTS: The estimated cumulative exposure to dust was strongly positively related to erythrocyte catalase activity and strongly negatively related to Cu++/Zn++ SOD activity only in miners exposed to high dust concentrations for > or = 14 years at the time of the study (F tests p = 0.006 and p = 0.004 respectively). Moreover, catalase activity was strongly related to the severity of CWP expressed as five subgroups of ILO profusion grades (F test p = 0.003); the greatest difference in the mean values was found between the group of 1/1 to 1/2 ILO profusion grades and the group of 2/1 to 3/3 ILO profusion grades. CONCLUSION: These results are in good agreement with the hypothesis that production of reactive oxygen species may be an important event in the exposure to coal mine dusts and the severity of CWP. Erythrocyte catalase and Cu++/Zn++ SOD activities are more closely related to recent exposure to high dust concentrations than to cumulative exposure, and could be considered as biological markers of exposure rather than as markers of early adverse biological effect.